2014
DOI: 10.1051/0004-6361/201423611
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology revealing trapped modes in KIC 10553698A

Abstract: The subdwarf-B pulsator, KIC 10553698A, is one of 16 such objects observed with a one-minute sampling rate for most of the duration of the Kepler mission. Like most of these stars, it displays a rich g-mode pulsation spectrum with several clear multiplets that maintain regular frequency splitting. We identify these pulsation modes as components of rotationally split multiplets in a star rotating with a period of ∼41 d. From 162 clearly significant periodicities, we are able to identify 156 as likely components… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 37 publications
3
24
1
Order By: Relevance
“…To investigate the latter possibility, we compared the results of a model atmosphere analysis using the hydrogen Stark broadening tables of Lemke (1997), employed in the present work, to those of Tremblay & Bergeron (2009), which include improved treatment of merging atomic energy levels. We found that improvements in Stark broadening theory may account for a shift of ∆ log g = +0.08 dex near 30 000 K (see, e.g., Østensen et al 2014;Telting et al 2014) in agreement with a shift of ∆ log g = +0.06 dex found at 40 000 K by Klepp & Rauch (2011). These systematic shifts are notable, but still cannot explain the model offsets apparent in Fig.…”
Section: Sample Propertiessupporting
confidence: 89%
“…To investigate the latter possibility, we compared the results of a model atmosphere analysis using the hydrogen Stark broadening tables of Lemke (1997), employed in the present work, to those of Tremblay & Bergeron (2009), which include improved treatment of merging atomic energy levels. We found that improvements in Stark broadening theory may account for a shift of ∆ log g = +0.08 dex near 30 000 K (see, e.g., Østensen et al 2014;Telting et al 2014) in agreement with a shift of ∆ log g = +0.06 dex found at 40 000 K by Klepp & Rauch (2011). These systematic shifts are notable, but still cannot explain the model offsets apparent in Fig.…”
Section: Sample Propertiessupporting
confidence: 89%
“…This is a relativistic effect in which the luminosity of an object is magnified when heading toward us but dimmed when moving away from us. It was observed in three other sdB binaries, KIC 11558725, KIC 7668647, and KIC 10553698 (Telting et al , 2014aØstensen et al 2014), which are similar to our object, therefore we looked for a flux variation on a time scale of an orbital period, P orb = 1.56 days (details are given below), and correlated it with radial-velocity variations. We have phased time-series photometric and radial velocity data to the inferior conjunction at BJD = 2 455 832.951 defined from the radial velocities and folded the data into 50 phase bins (Fig.…”
Section: Orbital Featuresmentioning
confidence: 85%
“…In the case of sdBV stars, it allowed us to detect multiplets in several of them (e.g., Telting et al 2012;Baran 2012b;Baran & Winans 2012;Reed et al 2014;Østensen et al 2014;Telting et al 2014a;Foster et al 2015). Encouraged by these results, we searched for equidistant peak formations that could be associated with rotationally split modes.…”
Section: Multipletsmentioning
confidence: 99%
“…While we initially intended to investigate the pulsation properties of the sdB star to describe it fully in similar terms to the many other interesting pulsators observed by the Kepler spacecraft (e.g., Baran et al 2012;Telting et al 2012;Reed et al 2014;Østensen et al 2014) and hopefully to be able to interpret the pulsation spectrum in terms of rotational multiplets, this was not feasible because of the complexity of the period and amplitude variability in many of the modes. For the purpose of deriving the eclipse timings, we were satisfied with removing only the most significant modes in the pulsation spectrum so that reliable eclipse timings could be measured and analyzed.…”
Section: Introductionmentioning
confidence: 99%